Là où s’échouent les destinées. Les prisons, dévoreuses de mémoires ? - Thibault Ducloux (Bulletin de l’Association de Géographes Français, 2021)
Confronted with prison confinement, prisoners are faced with several difficulties (family, social, financial, professional, judicial, administrative, etc.). If for the academic world these factors of vulnerability are obvious, another phenomenon needs to be explored: life in prison contradicts what social life has done to people. It attacks the reflexive and mnemonic economy of prisoners. As the months go by, they “lose” their words and bear witness to “memory lapses”. Memories become intertwined. The gap between past and future widens unreasonably. And yet, while there is every reason to believe that prison is a point in space where memories fade, others suddenly resurface. This state of affairs introduces the idea that the prison space acts as a revealer of a memory that is usually latent and diffuse in the rest of society. In this case, the religious is perhaps the best illustration of this.